Modelo lógico teórico, validado por especialistas, de um serviço de gerenciamento da Terapia Medicamentosa - Samuel Rodrigues Almeida e Sousa (2016)
A medication therapy management (MTM) service was structured aiming to optimize patients pharmacotherapy. In this, the pharmacist answers to a popular demand of prevention and resolution of drug related problems associated with its indication, effectivity, safety and convenience. There are no pre-established conditions for the implantation of MTM as a health service, nor a model to direct this process. Thus, this work aims to build a logical theoretical model of MTM services to fill this gap. For such, we used rounds of the Delphi method in order to obtain and analyze consensus from the opinions of MTM working specialists in the fields of teaching, management, research and practice. As a result, we elaborated a model containing 51 logically linked consensual items, which can serve as a theoretical basis for the construction of medication therapy management services in different scenarios of the health system.